Politics and International Investment - Rugman, Reviewed by: Alan M (Journal of International Business Studies, 2003)
Political risk has been a major concern of international business scholars up to the 1970s, yet this line of research has become rather quiet in recent years. Maybe, businesses found the world rather predictable between “Iran 1979” and “Indonesia 1997”. Yet, the end of the cold war has not eliminated political risk. Recently research has taken a more subtle perspective, incorporating as political risk small changes in local institutions that may affect investors' profitability.